Tiktok Application: A Study of Student Learning Concentration - Khairana Filzah Faradis; Reksiana Reksiana (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2022)
Lack of concentration in learning causes a decrease in the quality of learning, so it needs to be improved to improve student learning. This study aims to determine the learning concentration of students of the Tarbiyah Faculty of the Institute of Al-Qur'an Science (IIQ) Jakarta, which is influenced by the use of the TikTok application. With this, researchers can determine whether or not there is an effect on using the TikTok application. This research includes quantitative research with a descriptive method. The population in this study was 596 students, and the objects were all students of the Tarbiyah Faculty of the Institute of Al-Qur'an (IIQ) Jakarta, with a total sample of 86 people. The data collection technique uses a questionnaire. The results showed that, in the simple linear regression test, there was an influence between the X variable and the Y variable. That is <0.05= 0.007. It means that if the significance value is less than 0.05, it can be declared significant. Based on the result, the use of the TikTok application contributes 7.1% to the level of concentration in student learning, and other factors influence the rest.Kurangnya konsentrasi belajar menyebabkan menurunnya kualitas belajar, sehingga hal tersebut perlu ditingkatkan agar belajar mahasiswa lebih baik lagi. Penelitian ini bertujuan untuk mengetahui konsentrasi belajar mahasiswa Fakultas Tarbiyah Institut Ilmu Al-Qur’an (IIQ) Jakarta yang dipengaruhi oleh penggunaan aplikasi TikTok. Dengan ini peneliti dapat mengetahui ada atau tidaknya pengaruh penggunaan aplikasi TikTok. Penelitian ini termasuk penelitian kuantitatif dengan metode deskriptif. Populasi pada penelitian ini sebanyak 596 mahasiswa, yang dijadikan objek adalah seluruh mahasiswa Fakultas Tarbiyah Institut Ilmu Al-Qur’an (IIQ) Jakarta dengan jumlah sampel 86 orang. Adapun teknik pengumpulan datanya menggunakan angket atau kuesioner. Hasil penelitian menunjukkan bahwa, pada uji regresi linier sederhana terdapat pengaruh antara variabel X dengan variabel Y. Yaitu < 0,05 = 0,007. Artinya jika nilai signifikansi kurang dari 0,05 dapat dinyatakan signifikan. Dan dapat diketahui pula bahwa penggunaan aplikasi TikTok memberikan kontribusi 7,1% dalam tingkat konsentrasi belajar mahasiswa selebihnya dipengaruhi oleh faktor lain.